Website-Based Learning Media Using Weebly Water Cycle Material for Elementary School Teachers - Lebyana Norma Belinda; Yunus Abidin; Dede Trie Kurniawan; Harmawati (Universitas Pendidikan Ganesha, 2024)
21st-century learning activities: Students quickly get bored with monotonous learning. The learning media used is still traditional, so it needs to keep up with the times. This research analyzes website-based learning media for elementary school teachers using Weebly water cycle material. The type of research used is survey research with quantitative research methods. The subjects in this research were 100 elementary school teachers. The data collection technique used in this research is a questionnaire. The data analysis technique used is structural equation modeling-partial least square (SEM-PLS) with software using the SmartPLS 4.0 application. The research results show that Facilitating Conditions (FC) positively and significantly influence Behavior Intention (BI) in elementary school teachers' use of website-based learning media. Hedonic motivation (HM) positively and considerably influences elementary school teachers' behavior intention (BI) using website-based learning media. Social Influence (SI) positively and considerably influences behavior Intention (BI) in using website-based learning media for elementary school teachers. The research concludes that website-based learning media, using Weebly, positively influences elementary school teachers. This research implies that website learning media can adapt to different student learning styles because various media types are appropriate for student needs.